Ankylosing spondylitis and comorbidity: safety of long-term use of nimesulide - R. M. Balabanova (Современная ревматология)
Ankylosing spondylitis (AS) is a socially significant rheumatic disease that generally starts in young adults and, if untreated, often leads to temporary incapacitation, and by 40 years, and to disability. Despite the relatively young age of patients, the course of AS is accompanied by a number of comorbidities that most commonly include hypertension, dyslipidemia, and involvement of the gastrointestinal tract and kidney. The main group of drugs recommended for the treatment of the disease is nonsteroidal anti-inflammatory drugs (NSAIDs) that, when used long, exert analgesic, anti-inflammatory, and even disease-modifying effects on the one hand and can cause adverse reactions on the other. When choosing NSAIDs, one should consider not only the activity of the pathological process, but also the presence of comorbidities in the patient. The paper gives data on the efficacy and safety of nimesulide in AS. The drug has proven its efficacy and safety in various rheumatic diseases over nearly a quarter century of its use in Russia.